Accuracy Analysis of an Integrated Inertial Navigation System in Slow Maneuvers. Issue 2 (27th June 2017) - Nobahari, Hadi; Mohammadkarimi, Hamed
Abstract: In‐motion alignment of a strapdown inertial navigation system, during slow maneuvers, is studied. Terrestrial velocity is fed back to the navigation system to estimate and compensate for the navigation errors. Observability of the errors is analyzed since the integrated navigation system is not fully observable. Then, the accuracy bounds of the navigation system in different motion scenarios are obtained analytically. Also, in order to minimize the errors of the navigation system, special maneuvers are designed based on the analytical derivations. The analytical results, obtained using the linearized error model, are verified through nonlinear simulation of different maneuvering and non‐maneuvering scenarios. It is shown that the proposed analytical method can be used to predict the errors of the navigation system with a high level of accuracy. Copyright © 2017 Institute of Navigation